NUTRITIONAL INTAKE WITH THE EVENT OF ANEMIA IN PREGNANT WOMEN IN PADANGSIDIMPUAN CITY GENERAL HOSPITAL 2021 - Maisyaroh, Yusnina; Pebrianthy, Lola; Aswan, Yulinda (JURNAL IBU DAN ANAK, 2021)
A Pregnant woman will experience an increase in blood volume, this causes the need for iron to increase. The amount of iron needed during pregnancy is around 800-1000 mg, including to meet the needs of increasing red blood cells which require 300-400 mg of iron up to 32 weeks of gestation, to meet the needs of the fetus around 100-200 mg of iron . about 190 mg of iron will be lost during delivery. Common causes of anemia in pregnant woman are malnutrition ,loss of blood during past labor , chronic diseases such as intestinal woem tuberculosis and malaria . A person’s daily nutritional status is strongly influenced by the consumption of nutrients. The wrong or inappropriate nutritional intake for pregnant woman will cause health problems. The term malnutrition is defined as the wrong nutritional intake in the form of excess or insufficient intake, causing an imbalance between the needs and nutritional intake of pregnant woman. One of the easy, cheap, and fast determinants of nutritional status is LILA which reflects energy reserves so that it can reflect chronic energy deficiency in woman of childbearing age and pregnant woman .Objective : to determine the relationship between nutritional intake and the incidence of anemia ib pregnant woman at the Padangsidimpuan city at 2021.Methode : this research is included in the type of quantitative research with a descriptive analytical research design using a cross sectional study approach . with a total sample of 16 people using accidental sampling technique approach and the data was processes univariate and bivariate